2019
DOI: 10.1590/1983-40632019v4953688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding fungicide to mixtures of triazoles and strobilurins in the control of downy mildew and Asian soybean rust

Abstract: Fungicides used to control the Asian soybean rust are composed almost entirely of mixtures involving the systemic (triazoles) and meso-systemic (strobilurins) modes of action. However, to control the soybean downy mildew, only protective fungicides are available. The present study aimed to evaluate the effectiveness of fungicides with different modes of action in the control of downy mildew and Asian soybean rust. A field experiment was carried out in a randomized block design, with seven treatments [negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Downy mildew is a disease with a very high potential for dissemination (Silva et al, 2011). Zuntini et al (2019), state that downy mildew occurs in practically all soybean producing regions in Brazil, mainly in the vegetative phase of soybeans, corroborating with the data from the present experiment, since the first symptoms of downy mildew, in the first harvest, occurred at the beginning of the vegetative stage V3 of the crop and the maximum severity (1.12%) occurred in the reproductive stage R1. After stage R1 in the fourth evaluation, the disease declined.…”
Section: Discussionsupporting
confidence: 90%
“…Downy mildew is a disease with a very high potential for dissemination (Silva et al, 2011). Zuntini et al (2019), state that downy mildew occurs in practically all soybean producing regions in Brazil, mainly in the vegetative phase of soybeans, corroborating with the data from the present experiment, since the first symptoms of downy mildew, in the first harvest, occurred at the beginning of the vegetative stage V3 of the crop and the maximum severity (1.12%) occurred in the reproductive stage R1. After stage R1 in the fourth evaluation, the disease declined.…”
Section: Discussionsupporting
confidence: 90%
“…At the field level, warnings could include rainfall forecasts, which is also critical information for operational decision making as spray may be on hold if rain is very likely in the next day. This topic could be explored in future research, together with other factors which were not taken into account in our study such as differences in soybean maturity groups, host resistance, and more complex fungicide programs that involve different systemic fungicides combined with the use of multi-site and protectant fungicides, which have been used as an anti-resistance strategy (Godoy et al 2016;Zuntini et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a phytotoxic injury in the form of necrotic spots has been observed on leaves treated with this triazole-based fungicide. It has been reported that DMI fungicides including triazoles can cause phytotoxic damage on some soybean varieties, particularly under water stress or elevated temperatures [65,66]. However, Osiris ® with protective and curative activities is registered for controlling cereal rusts.…”
Section: Discussionmentioning
confidence: 99%